Impacts of coal dust from an active mine on the spectral reflectance of Arctic surface snow in Svalbard, Norway. Issue 3 (3rd February 2017) - Khan, Alia L.; Dierssen, Heidi; Schwarz, Joshua P.; Schmitt, Carl; Chlus, Adam; Hermanson, Mark; Painter, Thomas H.; McKnight, Diane M.
Abstract: Light‐absorbing particles (LAPs) in snow such as dust and black carbon influence the radiative forcing at the Earth's surface, which has major implications for global climate models. LAPs also significantly influence the melting of glaciers, sea ice, and seasonal snow. Here we present an in situ study of surface snow near an active coal mine in the Norwegian Arctic. We couple measurements of spectral hemispherical directional reflectance factor (HDRF) with measurements of LAPs characterized in two ways, as refractory black carbon using a Single Particle Soot Photometer and the total light absorption of LAPs measured with the Light Absorption Heating Method. The Snow Ice and Aerosol Radiation model was constrained by LAP measurements. Results were compared to observed spectral albedo measurements. Modeled and observed albedos were similar at the cleaner and more remote sites. However, the modeled spectral albedos do not fully account for the low spectral albedo measured next to the mine. LAP measurements also showed a large variation in particle sizes (tenths to tens of microns) related to transport distance of the particles from the mine. Here we find that LAPs from coal dust reduce the spectral HDRF by up to 84% next to the mine and 55% 0.5 km downwind of the mine. The coupling of extreme LAP observations (1 ng g −1 to 4863 ng g −1 ) with HDRF measurements from 350 to 2500 nm has facilitated the development of spectral band pairs, which could be used in the future to remotely assess LAPs in Arctic snow. Key Points: An active coal mine in the Norwegian Arctic has a measurable and significant impact on the reduction of surface albedo on nearby snow Increased mining exploration in the Arctic could exacerbate impacts due to coal dust Sites with high LAP concentration may be detectable by satellite remote sensing at specific wavelengths